2014
DOI: 10.1371/journal.pone.0100311
|View full text |Cite
|
Sign up to set email alerts
|

TC1(C8orf4) Regulates Hematopoietic Stem/Progenitor Cells and Hematopoiesis

Abstract: Hematopoiesis is a complex process requiring multiple regulators for hematopoietic stem/progenitor cells (HSPC) and differentiation to multi-lineage blood cells. TC1(C8orf4) is implicated in cancers, hematological malignancies and inflammatory activation. Here, we report that Tc1 regulates hematopoiesis in mice. Myeloid and lymphoid cells are increased markedly in peripheral blood of Tc1–deleted mice compared to wild type controls. Red blood cells are small-sized but increased in number. The bone marrow of Tc1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…MEFs are undifferentiated mesenchymal cells that may share stem cell-like characters. In our previous study, Tc1 −/− mice showed enhanced hematopoietic activity, but no enhancement of known hematopoietic growth factors was detected in bone marrow 29 . Together with data of this study, it might be postulated that Tc1 regulates bone marrow mesenchymal stem cell, which supports not only hematopoietic activity but also diverse systemic replenishment including adipose tissue 37 .…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…MEFs are undifferentiated mesenchymal cells that may share stem cell-like characters. In our previous study, Tc1 −/− mice showed enhanced hematopoietic activity, but no enhancement of known hematopoietic growth factors was detected in bone marrow 29 . Together with data of this study, it might be postulated that Tc1 regulates bone marrow mesenchymal stem cell, which supports not only hematopoietic activity but also diverse systemic replenishment including adipose tissue 37 .…”
Section: Discussionmentioning
confidence: 80%
“…Tc1 -deleted mice were described previously 29 . They had been backcrossed to C57BL/6 mice for 10 generations and kept in specific pathogen-free (SPF) animal facility at the Asan Institute for Life Sciences, Seoul, Korea.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study observed that the expression of TC1, β-catenin, and DNMT1 were correlated with each other, indicating that these three proteins might promote the activity of the Wnt signaling pathway in a synergistic manner. Recent studies revealed that TC1 plays a role in the regulation of stem cells, such as hematopoietic stem cells [ 16 ], adipocyte-derived stem cells [ 29 ], and liver cancer stem cells [ 22 ] via the Wnt/β-catenin signaling pathway or Notch signaling pathway. Therefore, TC1 may participate in tumorigenesis and the transformation of cancer stem cells, which require further studies.…”
Section: Discussionmentioning
confidence: 99%
“…TC1 is involved in the mitogen-activated ERK1/2 signaling pathway and promotes the G1- to S-phase transition of the cell cycle [ 15 ]. Recently, TC1 was also reported as a novel hematopoietic regulator in mice [ 16 ].…”
Section: Introductionmentioning
confidence: 99%